ASSESSMENT OF THE EFFECT OF FARMER FIELD SCHOOL ACTIVITIES ON THE LIVELIHOOD OF SMALLHOLDER RURAL COCOA FARMERS IN KWARA STATE, NIGERIA - FATAI, K. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
The study assessed the effect of farmer field school (FFS) on the livelihood of smallholder cocoa farmers in Kwara State, Nigeria. Descriptive survey design was used to conduct the research. A purposive sampling procedure was used to select 160 smallholder rural cocoa farmers who participated in the FFS activities in Kwara State. An interview schedule was used as an instrument for data collection. Data were collected on the socio-economic characteristics of the smallholder rural cocoa farmers, yield, income, house expenditure, household assets, and the constraints faced by the smallholder rural cocoa farmers. Data collected were analysed using means, frequency counts, percentages, and linear regression at a 0.05 level of significance. The result shows that 91.3% of the respondents were male and also there was an increase of 415kg of cocoa yield after participating in FFS. The result showed participating in FFS activities increased the yield, income, expenditures, and household assets of smallholder rural cocoa farmers. But statistically, there were no significant effects on yield, income, household expenditure, and household assets at p- values of 0.156, 0.892, 0.269, and 0.631 respectively. The findings conclude that FFS activities had no significant effects on yield, income, household expenditure, and household assets and these may be due to inadequate training facilitators faced by the smallholder rural cocoa farmers. The study recommends that the Kwara State Ministry of Agriculture should recruit, train, and retrain more facilitators and set proper monitoring and evaluation processes in other to make FFS activities more functional.